Supplemented Use of Pre-, Pro-, and Synbiotics in Severe Acute Pancreatitis: An Updated Systematic Review and Meta-Analysis of 13 Randomized Controlled Trials - Xu Tian; Xu Tian; Yuan-Ping Pi; Xiao-Ling Liu; Hui Chen; Wei-Qing Chen (Frontiers Media S.A., 2018)
Introduction: The role of pre-, pro-, and synbiotics supplemented to standard enteral nutrition in severe acute pancreatitis (SAP) remains unclear. We performed this updated meta-analysis to determine the value of pre-, pro- and synbiotics supplemented to standard enteral nutrition in predicted SAP.Methods: A systematic search in PubMed, EMBASE and Cochrane Central Register of Controlled Trials (CENTRAL) databases was performed. Eligible studies were randomized controlled trials (RCTs) that compared the effects of pre-, pro-, and synbiotics supplemented to standard enteral nutrition with control regime in predicted SAP patients. Risk ratio (RR) and mean difference (MD) with 95% confidence interval (95% CI) were used to express the estimates of dichotomous and continuous data respectively.Results: 13 RCTs comprising an aggregate total of 950 patients were eventually enrolled. Pooled results suggested that supplemented use of pre-, pro- and synbiotics effectively shorten the length of hospital stay in Chinese SAP cohorts (6 RCTs, MD = −5.57, 95% CI = −8.21 to −2.93, P < 0.001); however significant differences with regard to remaining clinical outcomes were not detected for all patients. Further analysis based on category of interventions including pre-, pro- and synbiotics also confirmed the findings to be reliable.Conclusions: Supplemented use of pre-, pro and synbiotics reduced the length of hospital stay in Chinese SAP cohorts. And thus, we concluded that pre-, pro- and synbiotics supplemented to standard enteral nutrition may be a potential option for the treatment of SAP patients. However, we also suggest designing further studies with large-scale and rigorous methods of addressing data to establish the effects and safety of supplemented use of pre-, pro- and synbiotics for SAP patients due to the presence of limitations.